Media penerbitan dan penyebaran idea identiti seni bina Malaysia: pengajaran daripada pergerakan arts and crafts di Britain dan Institusi Deutsche Werkbund di Jerman - Kosman, Kamarul Afizi (2006)
The crisis of an architectural identity which occurred in Malaysia since the last four decades have attracted several criticism and opinions from architectural notaries in this country. Despite many opinions by these individuals, most of the discussions about architectural identity has only revolved around design problems while the problems of the execution of these ideas is rarely revealed. The problems with idea dissemination pertaining to architectural identity through publication methods in Malaysia has been seen as one of the execution problems which contribute to the causes of the crisis in architectural identity. The problem comes when ideas from the prime movers of the discourse are not received by the general public. The purpose of this research is to identify the kinds of Malaysian architectural issues as discussed in the publication of books, magazines and newspapers and to find out how far the problems in dissemination of ideas about a national identity in Malaysian architecture has occurred through those particular mediums. Generally, the method of research used in this thesis rely on the historical methodology. The publication frameworks as derived from two important movers of modern architecture in Europe; the Arts and Crafts Movement in Britain and Deutsche Werkbund Institution in German, are used as the evaluation parameters in this study.